Are high strivers for justice more unjust when they react to a victim? Further evidence on the effects of the belief in a just world, of the innocence of the victim and of the persistence of suffering on secondary victimization - Correia, I. (2005)
This research aims to further explore the effects of Belief in a Just World (BJW), victim’s innocence and persistence of suffering on secondary victimization. Previous studies showed that an innocent victim whose suffering is more persistent is more secondarily victimized by high BJW participants than by low BJW participants (Correia & Vala, 2003). This study intends to replicate this finding and to overcome methodological limitations of these previous studies. Participants were 266 undergraduate students. The design was between-subjects 2 BJW (high, low) X 2 innocence of the victim (innocent, non-innocent) X 2 persistence of the suffering of the victim (more persistent, less persistent). The results supported partially the predictions. Theoretical as well as social implications of these findings are discussed.